Radioisotope instruments - Cameron, J. F. (John Foster); Clayton, C. G. (Colin Geoffrey) (Pergamon Press, 1971)
International Series of Monographs in Nuclear Energy, Volume 107: Radioisotope Instruments, Part 1 focuses on the design and applications of instruments based on the radiation released by radioactive substances. The book first offers information on the physical basis of radioisotope instruments; technical and economic advantages of radioisotope instruments; and radiation hazard. The manuscript then discusses commercial radioisotope instruments, including radiation sources and detectors, computing and control units, and measuring heads. The text describes the applications of radioisotope instruments in the industries, including mining and quarrying; agriculture, forestry, and fishing; manufacturing industries; transport and communications; and civil engineering constructions. The manuscript also focuses on legislation and codes of practice on the use of sealed radioisotope sources and control of radiation hazard. The book is a dependable reference for readers interested in radioisotope instruments.--Provided by publisher.